1989
DOI: 10.1111/j.1365-2885.1989.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of sulphadimidine, oxytetracycline and penicillin G in serum, synovial fluid and tissue cage fluid after parenteral administration to calves

Abstract: Drug concentrations in serum, synovial fluid and tissue cage fluid (TCF) in calves were measured after single i.m. doses of oxytetracycline hydrochloride (OTC), procaine penicillin G (PPG) and potassium penicillin G (KPG) and single i.v. doses of sulphadimidine (SDM) and OTC. For all drugs, concentration-time curves in serum and synovial fluid were not identical but they had similar profiles, with peak levels occurring at about the same time. Concurrent concentrations were lower in synovial fluid than in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
2
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 21 publications
0
8
2
3
Order By: Relevance
“…The elimination T ½ reported here for penicillin G in tammar wallabies (0.29 ± 0.08 h) is shorter than reported for a range of eutherian species (Bengtsson et al, 1989;Oukessou et al, 1990a;Oukessou et al, 1990b). This is reflected by the more rapid Cl in tammar wallabies; volumes of distribution are comparable.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The elimination T ½ reported here for penicillin G in tammar wallabies (0.29 ± 0.08 h) is shorter than reported for a range of eutherian species (Bengtsson et al, 1989;Oukessou et al, 1990a;Oukessou et al, 1990b). This is reflected by the more rapid Cl in tammar wallabies; volumes of distribution are comparable.…”
Section: Discussioncontrasting
confidence: 67%
“…The elimination T ½ reported here for penicillin G in tammar wallabies (0.29 ± 0.08 h) is shorter than reported for a range of eutherian species (Bengtsson et al. , 1989; Oukessou et al.…”
Section: Discussioncontrasting
confidence: 66%
“…Studies of the pharmacokinetics of drugs in interstitial fluid give further insight into drug disposition [1,2,5,17]. Cooke et al [5] successfully used microdialysis membranes with low molecular weight cut off that excluded large proteins to investigate the disposition of penicillin G in subcutaneous interstitial fluid after intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…The elimination half-life of the WAD goats administered sulphadimidine (t 1/2β =7.68 ± 0.72 hr) and sulphadimidine/piroxicam (t 1/2β =8.72 ± 0.84 hr) are lower than the elimination half-life of starved broiler chicken (t 1/2β =11.60 ± 0.72 hr), ducks (t 1/2β =9.0 ± 0.9 hr) sheep, 3.93 ± 0.61 hr, 4.50 ± 0.3 hr, 4.5 hr, 4.0 hr,3.28 hr (54,18,64,8,65), but higher than that of guinea fowl (t 1/2β =6.0 ± 0.9 hr), domestic chicken, t 1/2β =6.2 ± 0.8 hr, cow, 11.30 hr, 11.08 ± 2.68 hr, 14.5 hr, 10.53 hr administered intravenous sulphadimidine. However, Silvestri et al reported elimination half-life (8 hr) of sulphadimidine in cow [7,10,54,[64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%